Electron vs energy transfer in arrays featuring two Bodipy chromophores axially bound to a Sn(IV) porphyrin via a phenolate or benzoate bridge - Lazarides, Theodore; Kuhri, Susanne; Charalambidis, Georgios; Panda, Manas K.; Guldi, Dirk Michael; Coutsolelos, Athanassios G. (Inorganic Chemistry, 2012)
In this report we describe the synthesis of multichromophore arrays consisting of two Bodipy units axially bound to a Sn(IV) porphyrin center either via a phenolate (3) or via a carboxylate (6) functionality. Absorption spectra and electrochemical studies show that the Bodipy and porphyrin chromophores interact weakly in the ground state. However, steady-state emission and excitation spectra at room temperature reveal that fluorescence from both the Bodipy and the porphyrin of 3 are strongly quenched suggesting that, in the excited state, energy and/or electron transfer might occur. Indeed, as transient absorption experiments show, selective excitation of Bodipy in 3 results in a rapid decay (τ ≈ 2 ps) of the Bodipy-based singlet excited state and a concomitant rise of a charge-separated state evolving from the porphyrin-based singlet excited state. In contrast, room-temperature emission studies on 6 show strong quenching of the Bodipy-based fluorescence leading to sensitized emission from the porphyrin moiety due to a transduction of the singlet excited state energy from Bodipy to the porphyrin. Emission experiments at 77 K in frozen toluene reveal that the room-temperature electron transfer pathway observed in 3 is suppressed. Instead, Bodipy excitation in 3 and 6 results in population of the first singlet excited state of the porphyrin chromophore. Subsequently, intersystem crossing leads to the porphyrin-based triplet excited state. © 2012 American Chemical Society.